2022
DOI: 10.3390/cancers14153759
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CKAP2 Inhibits Proliferation, Migration, and Aggregate Formation in Aggressive Breast Cancer

Abstract: Loss of mitotic regulation is commonly observed in cancer and is a major cause of whole-chromosome aneuploidy. The identification of genes that play a role in the proper progression of mitosis can help us to understand the development and evolution of this disease. Here, we generated a list of proteins implicated in mitosis that we used to probe a patient-derived breast cancer (BC) continuum gene-expression dataset generated by our group by human transcriptome analysis of breast lesions of varying aggressivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…The copyright holder for this preprint this version posted October 27, 2023. ; https://doi.org/10.1101/2023.10.27.564280 doi: bioRxiv preprint segregation (16)(17)(18)(19). CKAP2 knock-down leads to spindle assembly defects (16) and CKAP2 overexpression has been associated with tumor development (20)(21)(22) and is negatively correlated with survival rates in cancer patients (23). Our recent in vitro reconstitution experiments have demonstrated that CKAP2 substantially increases microtubule nucleation and growth rates (24), however, whether and how CKAP2 regulates microtubule dynamics and chromosome segregation in cells has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 27, 2023. ; https://doi.org/10.1101/2023.10.27.564280 doi: bioRxiv preprint segregation (16)(17)(18)(19). CKAP2 knock-down leads to spindle assembly defects (16) and CKAP2 overexpression has been associated with tumor development (20)(21)(22) and is negatively correlated with survival rates in cancer patients (23). Our recent in vitro reconstitution experiments have demonstrated that CKAP2 substantially increases microtubule nucleation and growth rates (24), however, whether and how CKAP2 regulates microtubule dynamics and chromosome segregation in cells has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%